9 Routine use of glycoprotein IIB/IIIA inhibitors is associated with improved survival in primary PCI. (27th November 2017) - Orzalkiewicz, M; Hodson, J; Ludman, P; George, S; Doshi, SN; Khan, S; Mamas, M; Hildick-Smith, D; Townend, JN; Calvert, PA
Abstract : Background: The role of glycoprotein IIb/IIIa inhibitors (GPI) in primary PCI (PPCI) remains uncertain. We aim to compare patient outcomes between routine and selective GPI usage strategies. Methods: All consecutive PPCIs in England between January 2009 and April 2015 were prospectively recorded in the BCIS database. The cohort was divided into routine and selective GPI usage groups based on the responsible consultant's (RC) strategy. The primary endpoint was all-cause mortality, which was compared using Cox regression analyses. Results: We assessed 110327 PPCIs. Routine compared to selective GPI usage (defined as GPI used in ≥75% and≤25% PPCIs performed by RC, respectively) was associated with significantly decreased Kaplan-Meier estimated rates for all-cause mortality at one year of 9.7% vs 11.0% (p<0.001) (figure 1). After multivariable adjustment, routine use of GPI was associated with less mortality (hazard ratio [HR]=0.87, 95%confidence interval [0.82–0.91], p<0.001) and repeat PCI for acute coronary syndrome (HR=0.82 [0.76–0.88], p<0.001) during the median follow-up of 18 months (IQR 1.2–32.4). Subgroup analysis found the survival benefit of routine GPI use to be similar for different P2Y12 inhibitors (p=0.339). Conclusion: A strategy of routine GPI usage in patients undergoing PPCI was associated with lower all-cause mortality as compared to selective GPI usage.